The effect of ENEAS application in patients with endometriosis and its influence on the level of IL-8 and MCP-1 - Liang, Denghui; Zhang, Yuhong; Chen, Lihua; Shu, Lisha; He, Ying; Ma, Hui; Qiao, Mei; Wang, Na (Cellular and Molecular Biology, 2022)
Endometriosis is a gynecological disease that endometrial cells develop outside the uterus. This event happens when the endometrial glands grow outside the endometrium and uterine muscles, especially in the pelvis. Although endometriosis is widespread, the clinical manifestations of the disease are very different, and it is challenging to adapt to the conventional classification system to divide patients into homogeneous groups. Given the importance of endometriosis, a correct, accurate, and timely diagnosis of this disease can significantly prevent its complications. Using health-related software is one of these ways. Enhanced Endometriosis Archiving Software (ENEAS) is a web-based application based on one of the most widely used open-source database management systems (MySQL), allowing the direct link to other open-source software for data management and storage. In the current study, the effect of ENEAS application was considered in patients with endometriosis, and its influence on IL-8 and MCP-1 gene expression was evaluated. For this purpose, 100 women with endometriosis were divided into two groups of 50 patients. The first group (control group) was examined by a gynecologist and received medication and treatment. In the case group, their demographic and clinical information were entered into ENEAS software. To study the expression of the IL-8 gene and MCP-1 gene, after collecting 5 ml of blood samples in tubes containing anticoagulant, RNA extraction was performed by Total RNA Purification Kit (Cat. 17200, 37500, 17250). Then cDNA synthesis was performed for this purpose, and a Bioneer DNA synthesis kit (South Korea) was used. The results showed that the expression level of the IL-8 gene in the case group was significantly reduced compared to the control group (P = 0.035). MCP-1 gene expression was also decreased compared to the control group, but this decrease was not significant. Therefore, those who used this application for treatment had reduced expression of IL-8 and MCP-1 genes. This event indicates that this application has reduced the amount of inflammation caused by endometriosis with proper analysis.